Membangun Loyalitas Pelanggan Melalui Emotional Attachment dan Store Atmosphere dengan Customer Satisfaction Sebagai Mediasi Pada Pamella Supermarket - Febriawan, Muhammad Ihsan; Udayana, Ida Bagus Nyoman; Setiawan, Budi (Gorontalo State University, 2026)
This study have the purpose to determine how store atmosphere and customer engagement affect customer loyalty and customer satisfaction at Pamela Supermarket. This quantitative study uses purposive sampling technique with a sample size of 200 participants. Data was collected through a questionnaire provided via Google Form. Then, the data was processed using SPSS version 25, and the analysis was conducted with the assistance of a computer. Each sample used as a data source is an Indonesian who has purchased at Pamella Supermarket. The results of the study indicate that emotional attachment and has a positive effect on customer satisfaction with a significance value of 0.015 0.05, store atmosphere has a positive effect on customer satisfaction with a significance value of 0.000 0.05, but customer satisfaction does not have a positive effect on customer loyalty with a significance value of 0.748 0.05, and emotional attachment has a positive effect on customer loyalty with a significance value of 0.015 0.05, then the store atmosphere does not have a significant positive effect with a significance value of 0.057 0.05. Based on the existing research results, Pamella Supermarket should implement marketing strategies and maintain customer emotional attachment by improving the quality of interactions, consistent service, and a pleasant shopping experience to strengthen customer loyalty.